초등학교 1학년과 2학년 수학교과서가 제공하는 평면도형의 학습기회에 대한 기호학적 분석 - 조진우 (한국초등수학교육학회지, 24(1), 2020)
본 연구는 초등학교 1학년과 2학년 수학교과서가 제공하는 평면도형에 대한 학습기회를 기호학적 관점에서 분석한 결과를 보고한다. 2015 개정 수학과 교육과정에서 초등학교 1∼2학년에 포함된 평면도형에 대한 학습은 학교에서 다루어지는 기하교육의 기초가 된다는 점에서 특히 중요하다. 수학학습은 의미의 문제와 관련되고 의미에 관한 활동은 기호 활동으로 볼 수 있다는 점에서 그리고 기호학적 분석은 의미에 대한 문제를 정교하게 기술하고 기회를 제공할 수 있다는 점에서 기호학의 관점과 도구를 채택하고, 사용한다. 교과서 활동이 요구하는 기호작용에 대한 분석을 통해 교과서 활동이 제공하는 학습기회의 의의를 드러내 기술할 수 있고, 겉으로 유사해 보이는 학습기회가 어떻게 다른지를 파악할 수 있음을 확인하였다. 분석 결과를 바탕으로, 1학년과 2학년 수학교과서에서 제공되는 학습기회 사이의 연계성에 대해서 논의하였다. 마지막으로 본 연구의 결론 및 시사점 그리고 후속연구를 제안하였다. This study reports the results of analyzing the learning opportunities about the plane figures provided by the first and second grade mathematics textbooks. The plane figures that students learn during this period are important in that it serves as the basis for the later geometric education. With assumptions that mathematics learning is related to the problem of meaning and that meaning-related activity can be viewed as a symbolic activity, it adopts and uses the perspectives and tools of semiotics to analyze the learning opportunities provided by the mathematics textbook. The analysis of the semiotic process of the textbook activities revealed the significance of learning opportunities and helped to distinguish the seemingly similar learning opportunities. Based on the results of the analysis, I discussed the link between learning opportunities provided by grade 1 and grade 2 mathematics textbooks. Finally, the paper concludes with suggestions and conclusions and suggestions for further research. KCI Citation Count: 0